Theoretical Clues for a New Vision of Mediatic Reception from Migratory Experience - Concepción Sepúlveda, Luis (2011)
This article shows a new vision of Media Consumption for Communication Research through the relation between a host society and Diaspora. Immigrant’s Media Consumption is already one of the fields with less bibliography in Spain. Therefore, we show the importance of generating other lines of Research in Communication that approach the study of the new reality that is forming at present, in our society. Migrations put in question not only the traditional vision of the media experience from Spanish Research with a national and sedentary public, but also it reexamines the role of Mass Media aimed to immigrants.